IMPROVING THE STUDENTS’ SKILLS IN WRITING RECOUNT TEXT BY USING DIARY AT INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL HJ. FAUZIAH BINJAI - OKTAVI SARI, OLIVIA (Faculty of Tarbiyah nad Teacher Training, 2022)
This research was aimed to find out the implementation of diaey to improve the students‟ writing skiils in writing recount text. The subject of this study were 21 students at IX grade of SMPIT Hj.Fauziah Binjai.This research was conducted by using Classroom Action Research. The qualitative data were obtained from observation sheet and interview sheet. The quantitative data were obtained from test which carried out at the end of every cycles. the tests were given to the students in pre- test, post-test I and post-test II. The result of data analysis showed that the students‟ score increased from the first test, post-test of cycle I to the post-test of cycle II. It could be seen from the mean of pre-test was 58,80 There were 23,80% (5 students) who passed the Minimum Passing Grade (MPG). In the post test of cycle I, the mean was 66,14. There were 33,33% (7 students) who passed MPG. In the post test of cycle II, the mean was 85,77%.There were (18 students) who passed MPG. It indicated that was improvement of the students‟ skills in writing recount text through diary.